Weslandia - Fleischman, Paul. (Cambridge, Mass. : Candlewick Press, 1999)
Wesley's garden produces a crop of huge, strange plants which provide him with clothing, shelter, food, and drink, thus helping him create his own civilization and changing his life.
Keywords: Plants -- Fiction; Gardening -- Fiction; Civilization -- Fiction